Persuasive Action and Ideological Polarization in Congress. (1st July 2021) - Vann, Burrel
Abstract: What drives polarized voting in Congress? This article develops a persuasive action model which argues that polarization in Congress depends on the assertive capacities of social movements, the vulnerability of political officials, and the partisanship of the environments they represent. Using multilevel analyses, I demonstrate that endorsements by the Tea Party movement influenced an increase in extreme (conservative) voting among legislators in the 112 th Congress. These effects are strongest for vulnerable, freshman legislators representing amenable Republican contexts.